Duels of the rulers: the question of ritual communication - Piotr Tafiłowski (Przegląd Nauk Historycznych, 2016)
The paper seeks to explain the significance of the phenomenon, which were the duels of monarchs. They appear to be best understood if analyzed in the context of ritual communication. Challenges to monarchs to fight a duel, although none actually took place, were widespread gestures from antiquity to the modern times. They are known from many documented, literary (Iliad) and iconographic sources and also from chronicles. It appears, however, that historians have not so far devoted proper attention to them and failed to correctly interpret this problem and explain it adequately. The present study is an attempt to look at the subject from a new angle.